Pencerdasan Melalui Penyuluhan Pengelolaan Obat Dagusibu Sebagai Peningkatan Kualitas Kesehatan - Al Falih, Muhamad Rafli; Rakhmat, Devanzka Jaifar; Triyantoro, Ahmad Fauzan; Lioni, Kenza Septia; Indartuti, Kartika; Bayuaji, Reihan Padantya; Khairunnisa, Rahmadina Safa; Putri, Adelia Zenia; Febyanti, Dyah Ajeng; Fatha, Husein Rahman; Harimurti, Sabtanti (Universitas Muhammadiyah Yogyakarta, 2025)
The background of this study is the high rate of drug abuse in the community, which can cause adverse health effects if not properly managed. Counseling on the proper management and use of drugs is very important to increase public understanding of how to use drugs safely and effectively. One of the efforts made to achieve this goal is through the DAGUSIBU (Daya Penggunaan Obat Secara Bijak untuk Umum) program, which aims to educate the public on how to manage and use drugs properly. This study used a quantitative method with a pre-post test experimental design. The respondents of this study were 27 community members who attended DAGUSIBU counseling, and data were collected through questionnaires filled out before and after counseling was conducted. Data analysis was carried out with statistical tests to determine differences in the level of knowledge of respondents before and after counseling. The results showed an increase in participants' knowledge. The average score of participants' knowledge in the pre-test was 76.375, which increased to 81.375 in the post-test. Most respondents reported that they better understood how to choose appropriate medicines and how to use them wisely. The 47% increase in post-test scores indicates the effectiveness of the program in improving community understanding of medicine management. In conclusion, the DAGUSIBU counseling program was effective in improving the community's knowledge on drug management, thereby reducing the risk of drug abuse and supporting better public health.